Identifikasi Molekuler Bakteri Endofit Tanaman Karet (Hevea Brasiliensis) dan Aktivitasnya dalam Memproduksi Inhibitor Alfa Amilase - Vanisa Sri Elvani; Syauqi Susana Rahmani; Safrida Dwiningsih; Tetty Marta Linda; Windi Dona Fitri Fitri (Metamorfosa: Journal of Biological Sciences, 2023)
Endophytic bacteria are sized microorganisms found in plant tissues that are known to produce secondary metabolites, one of which is the ?-amylase inhibitor. Plant potential is closely related to endophytic microorganisms present in plant tissues. The study aimed to determine the potential of endophytic bacteria in rubber plants to produce ?-amylase inhibitors and to identify molecular using the 16S rRNA gene sequence. The isolates used were endophytic bacteria isolates L1M1.A2, L1M1.B4, and L2M1.A27. The activity of ?-amylase inhibitor was tested by in vitro and spectrophotometric measurements at a wavelength of 540 nm. Endophytic isolates with the highest inhibitory values ??were identified using the 16S rRNA gene sequence with primers 8F and 1492R. The results showed that the L1M1.A2 isolate produced 29.44% ?-amylase inhibitor and was identified as Bacillus proteolyticus with 99.86% homology. The potential of the L1M1.A2 isolate could be developed as a candidate for an antidiabetic drug.